Science-Industry-Linkages in China: Motivation, Models and Success Factors for Collaborations of MNCs with Chinese Academia - Ulrike Tagscherer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2015)
[Motivation and background ...] The presented report describes and analyzes the results of a survey among 30 foreign invested enterprises in China in 2014. The survey was conducted once before in 2011/2012 and the update in 2014 was specifically designed to create a better understanding of the recent dynamics in innovation in China, especially in the collaboration between MNCS and Chinese universities and research institutes. The main questions the survey wants to answer are: who are the key drivers for collaboration, what are the key success factors and which are the most recent developments in these industry-science-collaborations. The survey also answers the question of what policy makers could do to increase the collaboration and to reinforce spill-over effects into the Chinese science system as well as to create a supportive environment for MCNs R&D activities in China.
urn:nbn:de:0011-n-4149596
Keywords: 330